POLA PENDIDIKAN EKONOMI PADA KELUARGA PENGRAJIN ROTAN DEMI MEMPERTAHANKAN KEBERLANJUTAN USAHA DI DESA KARANG ASEM KECAMATAN PLUMBON KABUPATEN CIREBON - Aurel Margaretha; Hermansyah (FKIP Unswagati, 2024)
True education is an absolute necessity for every human being who is carried out consciously to form self-potential. This study aims at patterns of economic education in rattan craftsman families in order to maintain business continuity. This research uses descriptive qualitative method. Informants in this study were families of rattan craftsmen in Karang Asem Village, Plumbon District, Brebes Regency. Data collection techniques in this study are observation, interviews and documentation. The results of this study are (1) The profile of the family of rattan craftsmen in maintaining the sustainability of this business there are two families, namely the two sons rattan home industry and the Nayafa rattan home industry, the business of the two families is growing more and more demand from factories and from consumers outside the city, (2 ) The pattern of economic education in rattan craftsman families in maintaining business continuity in Karang Asem Village, Plumbon District, Cirebon Regency 2 can be obtained three supporting patterns, namely: habituation, advice and training for independence, (3) Factors that influence patterns of economic education in rattan craftsman families In maintaining business continuity in Karang Asem Village, Plumbon District, Cirebon Regency, there are three factors, namely: discipline, honesty and obedience to the rules.